Pengaruh Dukungan Organisasi Dan Kepuasan Kerja Terhadap Kinerja Pegawai Pada Bagian Umum Setda Kabupaten Tabanan - Ni Luh Gede Putu Purnawati; I Nyoman Resa Adhika; I Wayan Gede Antok Setiawan Jodi (LP3M Universitas PGRI Mahadewa Indonesia, 2019)
The purposes of this study were to analyze: (1) the influence of organizational support to the job satisfaction, (2) the influence of organizational support to the employee performance, (3) the influence of employee job satisfaction to the employee performance. The numbers of samples in this study were 58 employees at the General Section of the Regional Secretariat of Tabanan Regency. The technique of sample is Random Sampling and the data are collected using a questionnaire. The technique of analysis used is Path Analysis Model. The results of the study found that the organizational support gave positive effect to the employee job satisfaction; the organizational support gave positive effect to the employee performance, and (3) the employee job satisfaction gave positive effect to the employee performance. The implications of the results of this study are the organizational support need to be given maximally to improve the employee job satisfaction at the General Section of the Regional Secretariat of Tabanan Regency. If the job satisfactions of employees get increasing, it will be able to improve the Employee Performance at the General Section of the Regional Secretariat of Tabanan Regency.